Population Dynamics Brown Plant Hopper ( Nilaparvata LUGENS (Stal) On Rice Plants In The Outside Area Impact of Sidoarjo MUD - Faisol Humaidi; Didik Daryanto (Agricultural Science, 2020)
This study aimed abundance for brown plant hopper (bph) in rice plants against the presence in natural enemies to maintain productivity in rice plants. The study was conducted in the villages in Gempolsari, Penatar sewu and Sentul, Tanggulangin district, Sidoarjo, East Java in May 2019 to October 2019. The research was conducted using survey methods. The research location was selected using by purposive sampling method, which is the area with the highest percentage of attacks, has been attacked at least 3 times the growing season, Ciherang rice varieties, and was reported as brown plant hopper endemic area in 3 villages of Tanggulangin District, Sidoarjo. The results showed population abundance, percentage of attack rates, lowest intensity of brown plant hopper attacks occurred in Gempolsari village and the highest in Sentul village while the composition and abundance of natural enemies of brown plant hopper were dominated by odonata family then followed by families Salticidae, Tetragnathidae and Coccinellidae (Coccinela repanda).